PRELIMINARY STUDY ON CULTURING ZOOPLANKTON WITH THE APPLICATION OF BIOGAS SLURRY - SAIN, V.P.; SHARMA, O.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The purpose of this study was to evaluate the effect of biogas slurry on water quality and zooplankton production. No significant effects on water chemistry were observed, though zooplankton population was significantin all the treated cisterns. The highest (2630 Nos/) zooplankton population was observed in dose given G 500 mg/l followed by 750 and 250 mg/l with a population of 2320 and 1990 Nos/l respectively, whereas, control showed only 560 Nos/1.